MORALITY IN DIGITAL DEMOCRACY - Syarafina Dyah Amalia; Riris Ardhanaris; Tenang Haryanto (Universitas Borneo Tarakan, 2023)
AbstractDuring the COVID-19 pandemic in almost all countries of the world, human activities were physically completely paralyzed and replaced by new ways through the help of technology and digitalization. Starting from work, school, and other communication needs to be carried out online, the delivery of opinions and aspirations related to the government is also carried out through online methods. Through the digital world, especially on social media platforms, discussions about a policy or new hope for government can be carried out by anyone and at any time, of course, this is an ease in realizing democracy. But unfortunately, behind this convenience, there are several problems that arise due to too easy communication through the digital world. These problems include the misuse of social media as an opinion-raising tool for certain parties, widespread fake news with invalid sources, rampant use of inappropriate language in digital communication, and other forms of unlimited freedom that no one can contain when communicating digitally. The inadequacy of internet users creates a lack of ethics in the use of communication technology. Through this article, the author will examine the phenomenon of digital democracy in terms of morality. The research was conducted using the literature review method, and it is expected that the results of this research will have an impact on internet users, especially for policy making.Keywords: digitalization, democracy, morality